2023
DOI: 10.1038/s41586-023-06116-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cash transfers on adult and child mortality in low- and middle-income countries

Abstract: We performed analyses of changes in adult and child mortality associated with implementation of cash transfer programmes between 2000 to 2019, a study period when many countries introduced cash transfer programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In Table 8, we do find a small drop in the number of children who ever died by 2.5% points, similar to the Richterman et al. (2023) study. The average effect is borderline statistically significant at 10% and small in magnitude relative to the decrease that we find in the total number of children.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In Table 8, we do find a small drop in the number of children who ever died by 2.5% points, similar to the Richterman et al. (2023) study. The average effect is borderline statistically significant at 10% and small in magnitude relative to the decrease that we find in the total number of children.…”
Section: Resultssupporting
confidence: 87%
“…Another potential mechanism for the decrease in the number of children is that Juntos, by increasing income and healthcare utilization, decreased child mortality. Richterman et al (2023) use the DHS from 37 countries to show that cash transfers (averaged across conditional, mixed, and unconditional types) have led to a 8% decrease in child mortality under the age of 5, with smaller and statistically insignificant effect of 3% for conditional cash transfer programs only. A decrease in child mortality in our setting could, in turn, decrease the total number of pregnancies and children ever born needed to reach the ideal number of living children.…”
Section: Alternative Explanation: Child Mortalitymentioning
confidence: 99%
“…[ 12 ] which found that higher SES groups showed greater declines in HIV incidence from 1997 to 2018 in rural Uganda. More recently, the COVID‐19 pandemic has widened wealth inequality around the world, including in sub‐Saharan Africa [ 13 , 14 ], and our research adds to growing calls for structural anti‐poverty measures to improve population health [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…60 Comprehensive evidence from low-and middleincome countries suggests that cash transfers lower mortality for women and children younger than 5 years of age. 61 Quasi-experimental studies of the Earned Income Tax Credit have shown improvements in birth outcomes when income support amounts increased. 62 An evaluation of the SSI program using a regression discontinuity found that infants receiving SSI have reduced rates of both acute and chronic conditions across childhood, 63 though other evidence suggests that SSI payments during early childhood do not impact longer-term outcomes.…”
Section: Direct Cash Transfers: Consistent With Health System Values ...mentioning
confidence: 99%